STIMULATING THE AWARENESS OF PROSODY AS AN IMPORTANT FACTOR IN THE TEACHING OF FOREIGN LANGUAGES - CURRIE, Karen Lois (Intercâmbio, 2014)
RESUMO: O ensino das características suprasegmentais da fala raramente é incluído nos cursos de língua estrangeira e não é considerado prioridade na maioria dos programas universitários de ensino de Língua Inglesa. Na tentativa de estimular uma conscientização maior do papel da prosódia na comunicação efetiva em Língua Inglesa este artigo pretende utilizar exemplos de projetos de pesquisa desenvolvidos por alunos do primeiro ano de um curso de Licenciatura em Língua Inglesa para ilustrar a contribuição positiva de estratégias de ensino embasadas nos princípios da aprendizagem contextualizada, colaborativa e centrada no aluno. ABSTRACT: The prosodic characteristics of English are rarely included in university courses related to the teaching of foreign languages, nor is the teaching of English suprasegmentals considered a priority in the majority of ELT programs. Based on the principles of contextualized, collaborative and student-centered learning, this paper will use examples taken from a Prosody course taught to first year undergraduate students to illustrate how the inclusion of self-directed research projects can stimulate a growing awareness of the importance of prosody as an important factor in the teaching of effective language communication.